2019
DOI: 10.35680/2372-0247.1357
|View full text |Cite
|
Sign up to set email alerts
|

The impact of response rate on Hospital Consumer Assessment of Healthcare Providers and System (HCAHPS) dimension scores

Abstract: Patient experience measurement is receiving considerable attention from hospital executives, healthcare leaders, purchasers such as the Centers for Medicare and Medicaid Services (CMS), and patients. It is therefore appropriate and necessary to examine the methods of survey administration, and the analysis presented here seeks to understand the impact of one particular aspect of the measurement: response rate. Utilizing publicly reported HCAHPS (Hospital Consumer Assessment of Healthcare Providers and Systems)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 7 publications
1
20
0
1
Order By: Relevance
“…Response rate ensures reliability and credibility of the results and permits the research to be generalized to the larger population. [13] In the study done by Godden et al [14] on the impact of response rate on Hospital Consumer Assessment of Healthcare Providers and System (HCAHPS), they found that with increased response rates, hospitals received valuable feedback from a higher proportion of patients, creating a more representative sample of the total hospital patient population. While we could get feedback from an adequate number of patients in AFC, it was not possible to ensure feedback from a representative group in the PFC.…”
Section: Discussionmentioning
confidence: 99%
“…Response rate ensures reliability and credibility of the results and permits the research to be generalized to the larger population. [13] In the study done by Godden et al [14] on the impact of response rate on Hospital Consumer Assessment of Healthcare Providers and System (HCAHPS), they found that with increased response rates, hospitals received valuable feedback from a higher proportion of patients, creating a more representative sample of the total hospital patient population. While we could get feedback from an adequate number of patients in AFC, it was not possible to ensure feedback from a representative group in the PFC.…”
Section: Discussionmentioning
confidence: 99%
“…While our response rate of 21.1% for HCAHPS was comparable to the national average of 26.7%, it may not reliably represent our patient population. 15 Lastly, we had limited financial data. a Adjusted for age, primary insurance, race, Charlson comorbidity score, general or regional anesthesia, surgical service, and duration of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, participants are more likely to complete surveys if they are either very satisfied or very dissatisfied with the services provided. 16…”
Section: Discussionmentioning
confidence: 99%